Consumer Satisfaction Towards Fast Track Watches with Special Reference to Madurai City (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Satisfaction is the customers fulfillment response. It is a judgment that a product or a service feature, or the product or service itself, provides a pleasurable level of consumption related, fulfillment. In minimal technical terms, this definition can be translated to mean that satisfaction is the customers evaluation of a product or service in it . It is also important to recognize that, to measure the customer satisfaction at a particular point of time as if it were static, satisfaction is a dynamic, moving target that may evolve over the time, influenced by a variety of factors. Particularly when product usage or the service experience takes place over the time, satisfaction may be highly variable depending on which point the usage or experience cycle is focused on. This study focused on the customer satisfaction towards Fasttrack watches within Madurai district.The researcher followed convenience randam sampling method to collect data from 50 respondents. The researcher found that Majority of the respondents are aware about the various range of products provided by Fastrack watches through advertisements. The researcher also suggested that In order to improve its sales, ad promotion should be taken care, excellent customer care should be provided and also it should reduce its service time. The researcher concluded that gaining and maintaining consumer preference is a battle that is never really won. Continued and consistent branding initiatives that reinforce the consumers purchase decision will, over time, land the product in consumer preference sets. Attaining and sustaining preference is an important step on the road to gaining brand loyalty.